Rapid molecular diagnosis of von Willebrand disease by direct sequencing. Detection of 12 novel putative mutations in VWF gene - Corrales, Irene; Ramírez, Lorena; Altisent, Carme; Parra, Rafael; Vidal, Francisco (Thrombosis and Haemostasis, 2009)
Molecular diagnosis of von Willebrand Disease (VWD) is particularly complex. The autosomal von Willebrand factor gene (VWF) is large and highly polymorphic, and there is a highly homologous (>96%) partial pseudogene in chromosome 22. Because of these difficulties, application of molecular study of VWD to the clinical routine has been considerably delayed. Recent advances in sequencing technology and bioinformatics could convert direct sequencing of the complete VWF into a routine diagnostic tool for VWD, which is especially desirable in types 1 and 3. This study describes a highly optimized procedure in which all the coding and intronic flanking regions of VWF are amplified under identical thermocycling parameters in a ready-to-use PCR plate format. The entire sequencing procedure, from blood extraction to mutation identification, can be done within 24 hours, resulting in a simple, versatile, cost-effective strategy with little hands-on time requirements. To validate the method, we performed full-length VWF sequencing of 21 index cases including seven of each VWD type. A total of 30 VWF genetic variations were identified. Twelve of these sequence variations are new, including four missense, one nonsense, one insertion, the first insertion-deletion described in VWF, and 5 potential splice site mutations. To our knowledge, this is the fastest and most efficient protocol designed to date for complete sequencing of the VWF coding region in the molecular diagnosis of VWD.
Keywords: Automated DNA sequencing; molecular diagnosis; mutation analysis; von Willebrand disease; von Willebrand factor